Thermocatellispora soli sp. nov., isolated from hot spring soil - Thitikorn Duangupama; Pattama Pittayakhajonwut; Chitti Thawai (My University, 2018)
An aerobic, spore-forming, actinomycete, designated strain CHM3-46T, was isolated from soil in a hot spring pond located in Chiangmai province, Thailand. The strain exhibited taxonomic characteristics consistent with the genus Thermocatellispora. Strain CHM3-46T produced short, straight chains of warty spores on aerial mycelia. The presence of meso-diaminopimelic acid was observed in the cell-wall peptidoglycan. The whole-cell reducing sugars were glucose, mannose, galacose and ribose. The phospholipids comprised phosphatidylmethylethanolamine, hydroxyphosphatidylmethylethanolamine, phosphatidylethanolamine, hydroxyphosphatidylethanolamine, diphosphatidylglycerol, phosphatidylinositol, four phosphoglycolipids and three unidentified phospholipids. The predominant menaquinones were MK-9(H4), MK-9(H6) and MK-9(H8). 10-methyl C17 : 0, C16 : 0, C17 : 0 and iso-C16 : 0 were identified as the main cellular fatty acids. The G+C content of the genomic DNA was 73.2 mol%. Analysis of the 16S rRNA gene sequence showed that strain CHM3-46T belonged to the genus Thermocatellispora, exhibiting the highest similarity to Thermocatellispora tengchongensis YIM 77521T (98.5 %). Furthermore, a low DNA relatedness value (23.4 %±0.8) and several physiological and biochemical characteristic differences were detected between strain CHM3-46T and its closest relative. Based on the taxonomic data, strain CHM3-46T could be readily distinguished from its closest phylogenetic relative and represents a novel species, for which the name Thermocatellisporasoli sp. nov. is proposed. The type strain is CHM3-46T (=TBRC 7649T=NBRC 113148T).
Keywords: Strain (injury); genomic DNA; Diaminopimelic acid; Rhamnose; Diamino acid; Genomics and Phylogenetic Studies